Analisis Implementasi E-Procurement Pada Pengadaan Barang dan Jasa di Kepolisian Resor Kabupaten Sukoharjo - Kartikasari, Febrian Indah (Universitas Labuhanbatu, 2023)
Indonesia is recorded to have a Corruption Perception Index of 34 on a scale of 0-100 in 2022. This makes Indonesia ranked 5th most corrupt country in Southeast Asia. ICW recorded 579 corruption cases in Indonesia in 2022, of which the procurement of goods and services ranked first in the most corruption cases handled by the KPK with 266 cases.This study aims to determine the suitability of the implementation of e-procurement at Sukoharjo Police Station with applicable legal provisions, as well as identify supporting and inhibiting factors in the implementation of e-procurement at Sukoharjo Police StationThis research is a qualitative research with a human instrument approach that prioritizes natural and natural aspects. This research was conducted by a process of observation, documentation, and direct interviews with informants. Informants were determined using purposive techniques in which the sources of the research were selected from people directly involved in the running of E-procurement at the Sukoharjo Police Station. The results of this study show that the problems faced in the implementation of E-procurementÂ such as lack of electricity supply, system disruption, negligence of goods providers, and lack of local providers of goods and services..There are also supporting factors such as qualified human resources, communication, goals, environment, and executive compliance.Researchers designed outputs that can be used to support the running of E-procurement such as creating helpdesk teams, socializing local providers, improving systems, and collaborating with PLN to overcome the problem of lack of electricity supply.